2009
DOI: 10.2466/pr0.105.3.849-856
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Factorial Validity of the Revised UCLA Loneliness Scale: A Test of Competing Models in a Sample of Teachers

Abstract: Over the years, various studies addressing different populations have consistently raised concerns about the unidimensionality of the Revised UCLA Loneliness Scale. In the present study, the factorial structure of the scale was examined by comparing it to alternative models. In a sample of 1,157 French Canadian teachers, results of confirmatory factor analysis support a three-factor model solution. Support for the invariance of this model across sexes and teaching levels (i.e., elementary and high school) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
41
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 22 publications
4
41
0
1
Order By: Relevance
“…Confirmatory factor analysis results indicated that the UCLA LS3 had multidimensional structure. Multidimensionality of the previous versions of the UCLA has been supported by several researchers (Dussault et al, 2009;Mahon et al, 1995, McWhirter, 1990, Hartshorne, 1993 ''to clarify client's need and appropriate interventions'' (McWhirter, 1990, p. 56). Consistently, the multidimensionality of the UCLA LS3 is supported by Russell (1996).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Confirmatory factor analysis results indicated that the UCLA LS3 had multidimensional structure. Multidimensionality of the previous versions of the UCLA has been supported by several researchers (Dussault et al, 2009;Mahon et al, 1995, McWhirter, 1990, Hartshorne, 1993 ''to clarify client's need and appropriate interventions'' (McWhirter, 1990, p. 56). Consistently, the multidimensionality of the UCLA LS3 is supported by Russell (1996).…”
Section: Discussionmentioning
confidence: 97%
“…He found that the 2-factorial solution revealed better results than the other factorials structures on the basis of confirmatory factorial analysis. Conversely, Dussault et al (2009) found that the 3-factorial solution had better goodness of fit indices rather than the 1-factorial and the 2-factorial solution.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Dussault, Fernet, Austin, and Leroux (2009) examined the factorial validity of the Revised UCLA Loneliness Scale with a random sample of 1,157 Canadian teachers. In discussing the results the researchers addressed only the factorial structure of the scale.…”
Section: Studies Of Loneliness Involving Teachersmentioning
confidence: 99%
“…However, up to now their participation has been limited to purposes such as the measure of loneliness among children and teenagers, and validation of instruments (Dussault, Fernet, Austin, & Leroux, 2009;Galanaki & Vassilopoulou, 2007). Assessment of teachers' loneliness and its implications for the educational field are scarce.…”
Section: Introductionmentioning
confidence: 99%